Asymmetric C–H functionalization involving organocatalysis. Issue 24 (10th June 2015) - Zhao, Yong-Long; Wang, Yao; Luo, Yong-Chun; Fu, Xiao-Zhong; Xu, Peng-Fei
Graphical abstract: Abstract: The direct asymmetric functionalization of inert C–H bonds is one of the most challenging fields in current organic synthesis. As one of the main branches of asymmetric catalysis, several generic activation modes of organocatalysis have been successfully used to realize the asymmetric C–H functionalization reactions, such as CDC reactions, [1, 5]-hydride transfer reactions, β-functionalization of carbonyl compound. In this review, we are trying to give the readers an overview of the recent progresses of direct asymmetric organocatalytic C–H functionalization reactions.